الاسترا تيجية الجز ا ئرية لمواجهة التهديدات الصحية القادمة من منطقة الساحل الإفريقي - علاء الدين لصفر (جامعة المسيلة, 2025)
In an era where geographical boundaries no longer constitute barriers to the proliferation of health threats, and where the COVID-19 pandemic has demonstrated that neglecting health security may impose substantial costs upon nations across all dimensions, Algeria confronts a critical strategic challenge manifested in addressing a complex array of health threats emanating from the African Sahel region. This "arc of crises" represents a volatile zone characterized by a critical convergence of geographical, climatic, demographic, social, economic, political, and security factors, generating a perfect storm of diverse health threats encompassing lethal infectious diseases, devastating environmental hazards, and consequences of mass displacement and armed conflicts. The significance of examining this strategy derives both from its scientific contribution in providing comprehensive analysis of Algeria's integrated multi-instrument approach, and its practical utility in furnishing policymakers with an assessment of national strategy performance and effectiveness, while identifying strengths and vulnerabilities within the health security framework. The study originated from a central problematic questioning the effectiveness of Algeria's strategy for confronting health threats emanating from the Sahel region during the period 2013-2025, predicated upon a general hypothesis suggesting that Algeria's strategy demonstrates increasing commitment to enhancing health security through developing multiple instruments, though its overall effectiveness encounters challenges related to coordination, adaptation, and resource sustainability. Secondary hypotheses focus on the diversity and severity of health threats from the Sahel, Algeria's development of a graduated multi-instrument strategy, and the strategy's demonstrated effectiveness in constructing institutional frameworks while confronting challenges in integrated and sustainable operational implementation. Recognizing the gravity of these challenges, particularly following lessons learned from the COVID-19 pandemic that highlighted the substantial costs of overlooking health threats, Algeria has developed since 2013 a proactive, graduated, and multi-instrument health security strategy. This approach commenced with adopting International Health Regulations and the National Prevention Plan in 2013, followed by establishing the Multi-Sectoral Committee in 2015, developing cross-border health surveillance services during 2016-2024, culminating in the establishment of the National Health Security Agency in 2020. The evaluative study for the period 2013-2025, which relied upon the Joint External Evaluation (JEE 2022) and World Health Organization reports, concluded that this strategy may be characterized as "relatively effective." Algeria succeeded in constructing a robust legal and institutional framework with clear political will and considerable capabilities. However, qualitative analysis revealed disparities between ambitious legal and regulatory texts and actual operational implementation, indicating gaps in coordination, adaptation, and resource sustainability that may permit limited outbreaks or delays in optimal response. This necessitates developing an integrated national strategy for border health security, updating and digitalizing surveillance systems, enhancing capabilities at entry points and resources in the south, activating multi-sectoral coordination, and revitalizing health diplomacy and regional and international cooperation. The analysis emphasizes that health security represents a continuous process of construction and adaptation requiring strong political commitment, long-term investment, and comprehensive strategic vision.